Baryon-CDM isocurvature galaxy bias with IllustrisTNG - Barreira, Alexandre; Cabass, Giovanni; Nelson, Dylan; Schmidt, Fabian (Journal of cosmology and astroparticle physics, 2020)
We study the impact that baryon-CDM relative density perturbations δbc have on galaxy formation using cosmological simulations with the IllustrisTNG model. These isocurvature (non-adiabatic) perturbations can be induced primordially, if multiple fields are present during inflation, and are generated before baryon-photon decoupling when baryons did not comove with CDM. The presence of long-wavelength δbc perturbations in our simulations is mimicked by modifying the ratios of the cosmic densities of baryons Ωb and CDM Ωc, at fixed total matter density Ωm. We measure the corresponding galaxy bias parameter bδbc as the response of galaxy abundances to δbc. When selecting by total host halo mass, bδbc is negative and it decreases with mass and redshift. Stellar-mass selected simulated galaxies show a weaker or even the opposite trend because of the competing effects of δbc on the halo mass function and stellar-to-halo-mass relations. We show that simple modeling of the latter two effects describes bδbc for stellar-mass-selected objects well. We find bδbc =0.6 for M* = 1011 M⊙/h and z=0.5, which is representative of BOSS DR12 galaxies. For δbc modes generated by baryon-photon interactions, we estimate the impact on the DR12 power spectrum to be below 1%, and shifts on inferred distance and growth rate parameters should not exceed 0.1%.
Gesehen am 10.08.2022